Human pluripotent stem cells in contemporary medicine - S. A. Rodin (Исследования и практика в медицине)
Human pluripotent stem cells (hPSCs) are capable of indefinite proliferation and can be differentiated into any cell type of the human body. Therefore, they are a promising source of cells for treatment of numerous degenerative diseases and injuries. Pluripotent stem cells are also associated with a number of ethical, safety and technological issues. In this review, we describe various types of hPSCs, safety issues that concern all or some types of hPSCs and methods of clinical-grade hPSC line development. Also, we discuss current and past clinical trials involving hPSCs, their outcomes and future perspectives of hPSC-based therapy.